1994
DOI: 10.1111/j.1467-8624.1994.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Comprehension of Pretend Episodes: The Integration of Successive Actions

Abstract: In 3 experiments, children's comprehension of successive pretend actions was examined. In Experiment 1, children (25-38 months) watched 2 linked actions (e.g., a puppet poured pretend cereal or powder into a bowl, and then pretended to feed the contents of the bowl to a toy animal). Children realized that the pretend substance was incorporated into the second action. In Experiment 2, children (24-39 months) again watched 2 linked actions (e.g., a puppet poured pretend milk or powder into a container, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…If the distinction between real-world counterfactual reasoning and reasoning about other types of non-actual scenarios is a meaningful one, then it might be predicted that these two types of reasoning show different developmental trajectories. It is well-established that children are capable of reasoning about pretend and fictitious scenarios early in development, with 2-year-olds able to make certain types of judgments about pretend events (Harris, Kavanaugh, & Meredith, 1994;Harris & Kavanaugh, 1993). However, it is plausible that, because of its cognitive demands, real-world counterfactual reasoning does not emerge until later.…”
Section: When Does Real-world Counterfactual Reasoning Develop?mentioning
confidence: 99%
“…If the distinction between real-world counterfactual reasoning and reasoning about other types of non-actual scenarios is a meaningful one, then it might be predicted that these two types of reasoning show different developmental trajectories. It is well-established that children are capable of reasoning about pretend and fictitious scenarios early in development, with 2-year-olds able to make certain types of judgments about pretend events (Harris, Kavanaugh, & Meredith, 1994;Harris & Kavanaugh, 1993). However, it is plausible that, because of its cognitive demands, real-world counterfactual reasoning does not emerge until later.…”
Section: When Does Real-world Counterfactual Reasoning Develop?mentioning
confidence: 99%
“…In a recent study by Harris, Kavanaugh, and Meredith (1994), 2 and 3-year-olds demonstrated an understanding of the logical sequence of pretense episodes. For example, they predicted that an animal would become "milky" if pretend milk were poured over it.…”
Section: Pretense and Deceptionmentioning
confidence: 99%
“…Contrary to Harris et al (1994), Lillard (1991), and Gopnik and Slaughter (1991), Leslie (1988) considers pretense as an early precursor of children's understanding of the mind. He believes that, for example, when a child is playing with a banana pretending that it is a telephone, the child is simultaneously representing the situation as one that contains a banana (perceptually) and as one containing a telephone (pretense).…”
Section: Pretense and Deceptionmentioning
confidence: 99%
“…It is in fact controversial whether pretending is an intentional activity, at least if this means that pretending depends on something like specific fictive intentions [for a positive and a negative view on this, see respectively Currie (1990) and Walton (1990), who adopts the causal-inferentialist stance on pretence defended also by Harris et al (1994)]. Whatever the solution one gives to this problem, Friedman and Leslie (2007) have recently discussed some cases of pretence which are problematic in both pure 'behaving-as-if'-theories and the intentionalist 'behaving-as-if'-theories proposed by Rakoczy and Tomasello (2006).…”
mentioning
confidence: 98%
“…In their important study, Harris et al (1994) looked for children's ability to integrate successive pretend actions into a coherent causalinferential sequence. In one experiment, children ranging from 28 to 38 months saw a puppet pretending to pour milk from an empty milk container into a matchbox.…”
mentioning
confidence: 99%